Pengaruh Personal Capability dan Sikap Meboya Terhadap Kompleksitas Penyusunan Laporan Keuangan Berdasarkan SAK EMKM pada UMKM di Kabupaten Buleleng - Ni Luh Gede Yastini; Sunitha Devi (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the effect of personal capability and meboya attitude on the complexity of preparing financial reports based on SAK EMKM on MSMEs in Buleleng Regency. This study uses a quantitative approach. The population used is all MSMEs that already have business licenses in Buleleng Regency in 2022. The research uses purposive sampling. Based on the sampling method, the samples obtained were 167 productive MSMEs. The data source used is primary data using a questionnaire measured using a Likert and dummy scale. The data were then analyzed using descriptive statistical analysis, data quality test, classical assumption testing, and hypothesis testing with the SPSS v.25. The study found that (1) Personal Capability had a positive effect on the complexity of preparing financial reports based on SAK EMKM; and (2) Meboya's attitude had a negative effect on the complexity of preparing financial reports based on SAK EMKM.